Methods of overcoming the language barrier in teaching English (Eurasian Journal of Philology Science and Education, 2019)
General principles and methods of overcoming the language barrier in teaching English, its components in their relationship and conditionality, focused our attention on a number of requirements,in the process of forming a foreign language communicative ability. At the same time, as is obviousfrom the discussion in the above paragraph, we did not directly touch on the methodological issues oforganizing content in specific training conditions, identifying parts or units in it that are correlated withcertain points in the dynamics of the learning process. Meanwhile, the question of determining themain organizational and methodological unit for the organization of the content of teaching English,as methodological sources have shown, has attracted the attention of researchers for many years. Thetheme is called as such a unit. And we believe that the definition of the methodological status of thetopic as the main organizational-substantive unit of instruction, within which the process of activatingthe cognitive-communicative activity of students is carried out, is currently relevant. Linguistic andlinguistic competences are formed indirectly, through the content of educational material and in theprocess of acquiring communicative competence. The formation of communicative competence isprovided by interconnected training in all four types of speech activity based on a communicative andfunctional approach. At the same time, the need to include communicatively significant speech situations in the training content is rightly emphasized. It is also indicated that the selection of language General principles and methods of overcoming the language barrier in teaching English, its components in their relationship and conditionality, focused our attention on a number of requirements,in the process of forming a foreign language communicative ability. At the same time, as is obviousfrom the discussion in the above paragraph, we did not directly touch on the methodological issues oforganizing content in specific training conditions, identifying parts or units in it that are correlated withcertain points in the dynamics of the learning process. Meanwhile, the question of determining themain organizational and methodological unit for the organization of the content of teaching English,as methodological sources have shown, has attracted the attention of researchers for many years. Thetheme is called as such a unit. And we believe that the definition of the methodological status of thetopic as the main organizational-substantive unit of instruction, within which the process of activatingthe cognitive-communicative activity of students is carried out, is currently relevant. Linguistic andlinguistic competences are formed indirectly, through the content of educational material and in theprocess of acquiring communicative competence. The formation of communicative competence isprovided by interconnected training in all four types of speech activity based on a communicative andfunctional approach. At the same time, the need to include communicatively significant speech situations in the training content is rightly emphasized. It is also indicated that the selection of language